Hepcidin modulation in human diseases: From research to clinic - Piperno, Alberto (The WJG Press and Baishideng, 2009)
By modulating hepcidin production, an organism controls intestinal iron absorption, iron uptake and mobilization from stores to meet body iron need. In recent years there has been important advancement in our knowledge of hepcidin regulation that also has implications for understanding the physiopathology of some human disorders. Since the discovery of hepcidin and the demonstration of its pivotal role in iron homeostasis, there has been a substantial interest in developing a reliable assay of the hormone in biological fluids. Measurement of hepcidin in biological fluids can improve our understanding of iron diseases and be a useful tool for diagnosis and clinical management of these disorders. We reviewed the literature and our own research on hepcidin to give an updated status of the situation in this rapidly evolving field.